Falling admissions to hospital with febrile seizures in the UK. Issue 8 (29th March 2019) - Mccrorie, Kirsty; Thorburn, Joshua; Symonds, Joseph; Turner, Stephen W
Abstract : Objectives: There was a reduction in febrile seizure admissions in Scotland after 2008. Our hypothesis was that a similar trend would be seen in other countries. Methods: We obtained the number of febrile and non-febrile seizure admissions in England and Scotland 2000–2013 and the incidence of all seizure admissions 2000–2013 in European countries. We compared the incidence of admission for febrile seizure (Scotland and England) and all seizures (all countries) between 2000–2008 and 2009–2013. Results: The incidence of febrile seizure admissions per 1000 children in 2009–2013 was lower than 2000–2008 in Scotland (0.79 vs 1.08, p=0.001) and England (0.92 vs 1.20, p<0.001). The incidence of all seizure admissions (but not non-febrile seizures) was lower in 2009–2013 compared with 2000–2008 in Scotland (1.84 vs 2.20, p=0.010) and England (2.71 vs 2.91, p=0.001). Across 12 European countries (including the UK), there was no difference in all seizure admissions after 2008. We explored the possibility that the fall was related to the introduction of routine pneumococcal vaccination in 2006 but there were insufficient data. Conclusion: A fall in admissions for febrile (but not afebrile) seizures after 2008 in Scotland and England explains a fall in all emergency admissions for seizure. A fall in all seizure admissions has not occurred in other European countries, and more research is required to understand the different outcomes in the UK and non-UK countries.